Lead dust removal using electrostatic agglomeration. (August 2019) - Wang, Fang; Li, Mingjun
Abstract: PM2.5 (particulate matter smaller than 2.5 microns) emitted from non-ferrous metal smelting is a significant contribution to variety of heavy metals in the atmosphere. Previous studies found that, Pb, as and its oxide is mainly concentrated in PM2.5, or even PM1.0, which is seriously harmful to human health. The concern about fine particle emissions created a new problem to develop new methods to improve fine particle removal efficiency. Electrostatic agglomeration is one effective method to overcome the problem. In this study, chemical properties and size distribution of lead smelting dust was analyzed, and removal efficiency of fine particles in lead dust was tested using AC electrostatic agglomeration.